2013
DOI: 10.1155/2013/129736
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic, Anti-Inflammatory and Anticancer Activities of Extra Virgin Olive Oil

Abstract: Background. In folk medicine, extra virgin olive oil (EVOO) is used as a remedy for a variety of diseases. This study investigates the in vivo antinociceptive, anti-inflammatory, and anti-cancer effects of EVOO on mice and rats. Materials and Methods. In this experimental study, using the acetic acid-induced writhing and formalin tests in mice, the analgesic effect of EVOO was evaluated. Acetylsalicylic acid and morphine were used as standard drugs, respectively. The anti-inflammatory activity was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 42 publications
(45 reference statements)
4
21
0
Order By: Relevance
“…The results showed that the intraplantar injection of carrageenan into the mice hind paws induced progressive increase in the edema volume in the positive control as an inflammatory response up to the 4th h, when compared with the negative control group. This observation was coincident with the results of previous studies …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results showed that the intraplantar injection of carrageenan into the mice hind paws induced progressive increase in the edema volume in the positive control as an inflammatory response up to the 4th h, when compared with the negative control group. This observation was coincident with the results of previous studies …”
Section: Discussionsupporting
confidence: 93%
“…The results of this work revealed that the highest number of writhes was counted in the positive control group. This finding was documented by previous studies . We found also that IBU at a dose of 100 mg/kg significantly decreased the number of writhes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…16 The acetic acid-induced writhing test is a sensitive screening assay that is commonly used to study both central and peripheral antinociceptive responses, 27 whereas the formalininduced paw licking test is well established in the elucidation of a compound's mechanism of action at both the peripheral and central levels, where the early phase is characterized by neurogenic pain as a result of direct nociceptors stimulation in the paw and the late phase is characterized by inflammatory pain response due to the release of algogenic substances from damaged tissues. 28 Data obtained from the present study revealed that both liposome-encapsulated and free-form diclofenac exhibited dose-dependent pain inhibitory activities that were characterized by a significant reduction in writhing effect. Further evaluation via the formalin test suggested that liposome-encapsulated diclofenac is more effective in suppressing inflammatory pain and that stronger peripheralmediated antinociceptive activity could be attained using the present liposomal formulations.…”
Section: Discussionmentioning
confidence: 57%
“…europaea contains exogenous antioxidants with various benefits. Olives converted to Extra virgin olive oil (Evoo) possessed analgesic, anti-inflammatory, and anticancer properties [111]. EVOO was reported to able to control the induction of Hsp70 serum levels, thereby reducing growth of cell due to fetal complications in pre-eclampsia [160].…”
Section: Olea Europaeamentioning
confidence: 99%